Farm performance analysis: Technical efficiencies and technology gaps of Nepalese farmers in different agro-ecological regions. (July 2018) - Khanal, Uttam; Wilson, Clevo; Shankar, Sriram; Hoang, Viet-Ngu; Lee, Boon
Abstract: This paper employs a stochastic metafrontier framework to examine technical efficiencies and technology gaps of Nepalese farmers in different agro-ecological regions. On average, the technical efficiency level derived from the regional frontier is 81%, from the metafrontier it is 57%, and the technological gap ratio is 70%. There is therefore a clear opportunity to improve the performance of farming households within regions through improving farmer's education, farming experiences, and by adopting climate change adaptation practices. Also indicated is that agricultural policies should be developed to reduce the technology gap between specific regions and the overall agricultural sector. In this context, this study highlights the need to improve farmers' access to agricultural markets, livelihood diversification and strengthening social capital such as farmers' participations in relevant agricultural organizations.